Shāh Abdul Latīf, his life and work : a study of sociocultural and literary situations in eighteenth century Sindh (now in Pakistan) - Jotwani, Motilal Wadhumal, 1936- (Publication Division, University of Delhi, 1975)
On the life and works of the Sindhi Sufi poet Shah Abd al-Latif, ca. 1689-ca. 1752.